Morphological aspects and germ cells of male reproductive tract of river stingray, Potamotrygon amandae - Jacik, Stefhani Cristina Chan; Aquino, Julia Bastos de; Melo, Luana Felix de; Rodrigues, Rosângela Felipe; Melo, Alan Peres Feraz de; Miglino, Maria Angélica; Rici, Rose Eli Grassi (Acta Scientiarum. Biological Sciences, 2023)
The family Potamotrygonidae are the only species of stingrays restricted to fresh water and located exclusively in South America. The objective of this research was to analyze the morphological aspects and germ cells of the male reproductive tract of Potamotrygon amandae. The samples were fixed in 10% formalin, and then dehydrated in an ascending ethanol series (70 to 100%). To carry out light microscopy analyses, they were embedded in paraffin, cut and stained; as for scanning electron microscopy analyses, the samples were dried, glued in metallic bases and metalized. The gross morphology consisted of the following paired organs: testis, epididymis, deferent duct, Leydig gland, seminal vesicle, clasper, and the clasper gland. Microscopically, several stages of spermatogenesis were observed in the testis, occurring in spherical follicles, similar to other stingrays. The epididymis was formed by one duct subdivided in various tubules. The deferent ducts were continuous with the epididymis, and the lumen was full of spermatozoa. The Leydig glands consisted of glandular units with eosinophilic content in the lumen of some, and the deferent ducts ran parallel to the ventral portion. The seminal vesicles possessed numerous compartments to store the sperm, with a wall similar to a hive, and the lumen was full of spermatozoa. Alcian Blue (AB) and Periodic Schiff-Acid (PAS) performed in the Leydig Gland, deferens ducts and seminal vesicle was positive only in the connective tissue, the cilia were PAS+ and the nuclei stained weakly for AB. The clasper gland was composed of unit glands and was covered with striated muscle externally. It stained very well with Periodic Schiff-Acid. The morphological aspects of the male reproductive tract of Potamotrygon amandae were similar to other stingrays.